Empathy Development Among Generation Z in the Era of Artificial Intelligence: A Hadith Perspective - Nisa, Ainun; Murtadho, Ali; Supriadi, Nanang; Pahrudin, Agus (Ahlussunnah: Journal of Islamic Education, 2026)
The development of Artificial Intelligence has transformed Generation Z’s patterns of social interaction and raised moral challenges in the form of declining social sensitivity and a decrease in the quality of human interaction. This situation calls for strengthening moral education focused on fostering empathy. This study aims to analyze the values of empathy in the hadith and their relevance to the character development of Generation Z in the era of Artificial Intelligence. The study employs a qualitative approach using content analysis of hadiths related to empathy. The analysis involves the process of hadith authentication (takhrij), evaluation of hadith authenticity, and fiqh al-hadith interpretation to understand their meaning and relevance in a contemporary context. The results indicate that the examined hadiths are authentic and contain values of empathy, such as the ability to understand others’ circumstances, social concern, compassion, and human solidarity. These values are relevant in addressing the challenges of social interaction, which is increasingly mediated by digital technology and Artificial Intelligence. This study demonstrates that hadith-based moral education can serve as an ethical foundation for developing empathy in Generation Z, thereby fostering a generation that is morally upright, socially responsible, and wise in utilizing technology.